Analisis Pengungkapan Green Accounting pada Sustainability Report PT Sinergi Gula Nusantara - Pradita Andina Kurnia Putri; Titiek Rachmawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Environmental challenges and increasing regulatory demands have encouraged Indonesian companies to enhance environmental accountability through sustainability reporting. However, environmental disclosures in Indonesia remain largely descriptive and provide limited measurable information, particularly in relation to green accounting practices. This study aims to analyze the disclosure of green accounting in the 2023 Sustainability Report of PT Sinergi Gula Nusantara (SGN), a state-owned enterprise in the food sector and recipient of the 2024 Asia Sustainability Reporting Rating (ASRRAT), and to examine how the principles of accountability and transparency are reflected in such disclosures. This research employs a qualitative descriptive approach using document analysis of the sustainability report and semi-structured interviews with internal parties involved in report preparation. The analysis is guided by POJK No. 51 of 2017, GRI Standards 2021, and the concept of green accounting. The findings indicate that PT SGN has disclosed green accounting practices through environmental management activities, including energy and water efficiency, waste utilization, biomass use, and emission control, demonstrating compliance with sustainability reporting regulations and standards. Nevertheless, the disclosures remain predominantly narrative, with limited integration of quantitative environmental cost information. This study contributes to the literature by providing in-depth qualitative evidence of green accounting disclosure practices in a state-owned enterprise within the food industry.